Kesaksian Non Muslim dalam Perkara Perceraian menurut Pendapat Hakim di Pengadilan Agama Bandung - Ahmad Nabil Atoilah; Bayu Alif Ahmad Yasin (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
Islamic law one of the requirements to be a witness is Islam, but the Procedural Law of Religious Courts does not regulate the Islam of a witness. Terms of Islam are getting responses from various parties, especially the judges. The judge has his own opinion about the witness who must be Muslim, and that is different as formulated by the scholars. The issue of non-Muslim testimony in the case of divorce of judge opinion on the testimony of non-Muslims so that their testimony is accepted and declared valid as Islamic law which refers to Law no. 7 since 1989, since the enactment of the Law, the Procedural Law of Religious Courts is allowed to apply the procedural law applicable in the General Courts as the Law of the Program, namely HIR and R.Bg.